Treatment of aggressive prolactinoma with temozolomide: A case report and review of literature up to date. Issue 47 (November 2017) - Chen, Cheng; Yin, Senlin; Zhang, Shizhen; Wang, Mengmeng; Hu, Yu; Zhou, Peizhi; Jiang, Shu
Abstract: Rationale: Aggressive pituitary adenomas and pituitary carcinomas are rare and demand multiple treatment strategies. Temozolomide, an orally active alkylating chemotherapeutic agent, has recently been recommended as a salvage medication for refractory pituitary adenomas or carcinomas. Patient concerns: A 17-year-old male presenting with aggressive prolactinoma that continued to progress despite surgery, gamma knife, and dopamine agonists. Diagnoses: The diagnosis of refractory aggressive prolactinoma was made on the basis of clinical findings and the lack of efficacy of conventional treatment. Interventions: The patient received the most frequently recommended regimen of temozolomide treatment for 22 cycles. Outcomes: Temozolomide resulted in a remarkable shrinkage of tumor mass and inhibition of prolactin secretion and this patient's clinical condition improved progressively. Lessons: Temozolomide can be used as a salvage treatment to refractory pituitary tumors and o(6)-methylguanine-DNA methyltransferase (MGMT) status is a significant predictor to the effectiveness of temozolomide based on the existing literature.